Odor is linked to adrenocortical function and male ornament size in a colonial seabird. (2nd April 2018) - Douglas, Hector D; Kitaysky, Alexander S; Kitaiskaia, Evgenia V
Abstract : This study reports on a relationship between a chemical signal, physiological condition, and a putative signal of dominance in the crested auklet, a colonial seabird of Alaska and Siberia. This species emits a citrus-like odorant during the breeding season. Crest size was correlated with odorant emissions in males. Stress responses were correlated with odorant emissions in females. Our data suggest that odorants could serve as an assessment signal, offering novel evidence for the significance of odorants in birds. Abstract: Crested auklets ( Aethia cristatella ), colonial seabirds of Alaska and Siberia, emit a citrus-like odorant from wick-like feathers. We examined whether the odorant emission is linked to adrenocortical function and correlated with size of the crest feather ornament. Conventional signals like the size of crest ornament are inexpensive to produce and thus may be prone to deception. However, assessment signals such as the odorant could be more reliable if they impose costs and more proximate since they are continually produced. This may be the case for the crested auklet's volatile aldehyde odorant. The signal is composed of highly volatile chemicals that appear to be products of fatty acid metabolism. Adrenocortical function helps to mobilize endogenous resources for metabolism. Elevation of corticosterone may be needed to sustain a reliable chemical signal, but there are physiological costs for prolonged elevation of circulating corticosterone. We predicted that higher odorant emissions would be correlated with larger crest ornaments. Furthermore, we predicted that odorant emissions would be linked to adrenocortical response. Octanal, the most abundant compound in the citrus-like odorant, was positively correlated with crest size ( r = 0.37) in males, and adrenocortical response explained 42% of the variation in octanal emissions, after controlling for stage of the breeding period. Adrenocortical response was positively correlated with octanal emissions ( r s = 0.57) in females. We conclude that dominant individuals with greater capacity to mount a more robust stress response may have greater capacity to sustain odorant secretions.